2020
DOI: 10.1111/joor.12947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intra‐oesophageal acid infusion and a stress task on masseter muscle activity and autonomic nervous activity in wakefulness

Abstract: Background: Gastroesophageal reflux disease may be an important risk factor for awake bruxism. Additionally, it has been known that a psychological stress task affects masseter muscle activity, and autonomic nervous system (ANS) activity modulation induces masseter muscle activity.Objectives: This study aimed to investigate whether task-induced stress and experimental oesophageal acid infusion increase masseter muscle activity and alter ANS activity, compared to rest task and oesophageal saline infusion, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the same way, the association between GERD and AB was previously verified 92 . Intra‐oesophageal acid infusion in health adult men while reading a book quietly, and while performing calculation, as a stress task, also increased masseter muscle activity 95 …”
Section: Bruxism and Gerdmentioning
confidence: 54%
See 1 more Smart Citation
“…In the same way, the association between GERD and AB was previously verified 92 . Intra‐oesophageal acid infusion in health adult men while reading a book quietly, and while performing calculation, as a stress task, also increased masseter muscle activity 95 …”
Section: Bruxism and Gerdmentioning
confidence: 54%
“…92 Intra-oesophageal acid infusion in health adult men while reading a book quietly, and while performing calculation, as a stress task, also increased masseter muscle activity. 95 A narrative review suggested that tooth wear is associated with dental sleep disorders oro-facial pain, oral dryness, GERD and SB, considering that SB is indirectly associated with chemical tooth wear through GERD. 96 Regardless of this, in long-term GERD cases, SB is associated with severe dental wear.…”
Section: B Ruxis M and G Erdmentioning
confidence: 99%
“…Regarding GERD, SB is considered a possible protective factor for the disease 11 , 14 , 17 , 18 . This hypothesis describes that interdental contact from SB would activate the mechanoreceptors of the periodontal ligament, stimulating salivary secretion and neutralizing the acidic pH of the oral cavity 11 , 14 , 17 , 18 . Polysomnographic studies that evaluated patients with sleep bruxism and GERD support this hypothesis 11 , 14 , 17 , 18 .…”
mentioning
confidence: 99%
“…This hypothesis describes that interdental contact from SB would activate the mechanoreceptors of the periodontal ligament, stimulating salivary secretion and neutralizing the acidic pH of the oral cavity 11 , 14 , 17 , 18 . Polysomnographic studies that evaluated patients with sleep bruxism and GERD support this hypothesis 11 , 14 , 17 , 18 . More studies need to be carried out to establish and understand this relationship.…”
mentioning
confidence: 99%